Uptake of Micro and Macronutrients in Relation to Increasing Mn Concentrations in Cistus salvifolius L. Grown in Hydroponic Cultures - Figlioli, F.; Memoli, V.; Maisto, G.; Spagnuolo, V.; Giordano, S.; Leidi, E. O.; Oliva, S. Rossini (Journal of Environmental Accounting and Management, 2026)
Mining and smelting activities can alter the ecosystem degrading vegetation and landscape, causing loss of soil fertility and changes in hydrology and microclimate. The mining area of Rio Tinto is one of the largest metallic sulfide deposits in the world, extending to southern Portugal and the Rio Tinto region (Huelva, SW Spain). Soils, characterized by low pH, are strongly impoverished in macro- and micronutrients essential to the plant metabolism and contain very high concentrations of As, Cu, Fe, Mn, and Pb. The aim of this study was to evaluate the effects of increasing Mn concentrations (0, 50, 100, 200, and 300 mg /L) on the uptake of a set of micro and macro nutrients in Cistus salvifolius L., a species native of the Rio Tinto region. The plants, grown in hydroponic culture, were analyzed by AAS for elemental content and by SEM-XS ray microanalysis for element localization. The results of this study showed a stunted growth and ultrastructural alterations in the root of C. salvifolius, with the most evident damages occurring at the highest Mn concentration. Chemical analyses confirm that the higher the concentration in culture medium, the higher the uptake of Mn in plant tissue; both lower and higher Mn concentrations influence the absorption of other essential nutrients, as Fe, Zn, K, and Mg. The visible state of stress observed in plants grown with addition of 300 ppm Mn may therefore be due to such variations in the absorption of micronutrients and/or to theMn itself. Future studies should focus on possible synergistic and antagonistic activities of Mn versus other essential elements for proper plant development.